Factors Affecting to the Adoption of a 2-Way Interactive Video in Guangxi Zhuang Autonomous Region China - Qin, Minjun; Compan, Pongpan (Science, Technology, and Social Sciences Procedia, 2021)
This study aimed to analyze the factors influencing teachers to adopt the 2-way interactive video in Guangxi Zhuang Autonomous Region China. To make suggestions to encourage teachers to adopt the 2-way interactive video teaching level. This study applies the diffusion of innovations paradigm theory (Rogers, 1983) and the attitudes paradigm theory (Eargly & Chaiken, 1993). The sample size was 188 teachers from the Junhua Primary School and Shuangding Town Central Primary School of Xixiangtang District of Nanning. The research found that the factors affecting the adoption of a /-way interactive video in Guangxi Zhuang Autonomous Region China were as follows; 1) attitude goal, 2) habit, 3) self-identity outcome, 4) attitude toward the behavior, 5) normative outcome, 6) Utilitarian outcome, and 7) intention. The teacher agrees that the most factors that affect adopting a 2-way interactive video are the normative outcome, attitude toward behavior, and attitude toward the target. The minor factor was the intention. The research suggests that education departments and schools should create an educational informatization atmosphere conducive to 2-way interactive video application and provide policy support. Train teachers to use 2-way interactive video to improve the pertinence and effectiveness of training. Improve the frequency of teachers’ use of 2-way interactive video, and encourage teachers to improve their teaching level in the application.